Motivational interviewing in the treatment of psychological problems : applications of motivational interviewing - Arkowitz, Hal, ....-; Miller, William Richard, 1947-; Rollnick, Stephen, ....- (New York : Guilford Publications, 2015)
This authoritative guide, now significantly revised and expanded, has given tens of thousands of clinicians proven tools for helping clients resolve ambivalence and mobilize their energy, commitment, and personal resources for change. Leading experts describe ways to combine motivational interviewing (MI) with other treatments for a wide range of psychological problems, including depression, anxiety disorders, eating disorders, posttraumatic stress disorder, and others. Chapters illustrate the nuts and bolts of intervention, using vivid clinical examples, and review the empirical evidence base. Contributors show how to tailor MI to each population's needs, whether used as a pretreatment or throughout the course of therapy. This book is in the Applications of Motivational Interviewing series, edited by Stephen Rollnick, William R. Miller, and Theresa B. Moyers.